Provincial-level income inequality in the People's Republic of China: The role of human capital - Kristina Butaeva; Albert Park (Asian Development Bank (ADB), 2025)
In this paper, we conduct the first systematic empirical analysis of income inequality in the People's Republic of China (PRC) at the provincial level. Using data from the China Household Finance Survey (CHFS) and a semiparametric distribution model, we estimate Gini indices for a set of provincial-level administrative units in 2012, 2014, 2016, and 2018. We find that differences in the "prices" and "quantities" of human capital are important factors in explaining differences in inequality between these provincial areas. Our findings suggest that poor areas are highly disadvantaged compared with rich ones, as they face higher income and educational inequality, as well as higher returns to education, while at the same time exhibiting lower average educational attainment. We conclude that filling existing interprovincial human capital gaps and accelerating labor market integration through appropriate government policies could reduce spatial disparities in inequality levels across regions and overall income inequality in the PRC.
Keywords: D31; I24; O15; 330; income inequality; provinces; People's Republic of China; human capital